The effect of gamma irradiation on the fluorescence properties of 1, 4, 5, 8-naphtalisoimides. (May 2015) - Mazurak, Zbigniew; Wanic, Andrzej; Domański, Marian; Jarząbek, Bożena; Kaczmarczyk, Bożena; Konefał, Adam; Kądziołka-Gaweł, Mariola; Czaja, Maria
Abstract: The subject of our investigation was the intensity of the fluorescence of 1, 4, 5, 8-naphtalisoimides subjected to gamma radiation (the absorbed doses were 242 Gy, 1 kGy and 2.242 kGy). Dynamic changes of fluorescence intensity have been observed; the greatest relative increase of fluorescence intensity (and simultaneously, the least durable increase) occurs as a result of structural isomerisation. Highlights: The fluorescence intensity of γ irradiated naphtalisoimides is subject to change. These changes occur in three phases: increase, stabilisation. and decrease. E–Z structural isomerisation causes the greatest increase in fluorescence intensity.